Flexibility scores for energy transition pathways: Integrating socio-technical factors in a long-term energy market model. (15th April 2022) - Sheykhha, Siamak; Madlener, Reinhard
Highlights: A large-scale energy market model based on a system dynamics approach is proposed. The model is used to integrate the socio-technical dimensions of the energy system. There are synergies between the renewable energy mix and carbon capture technology. Two-factor learning effects do not increase system flexibility in the longer run. Enhanced flexibility of the market can be ensured without any governmental support. Abstract: The fundamental energy transition from a fossil-fuel-based energy system towards clean energy is not only about technological change but also about social-technical transition. Using a system dynamics model that includes socio-technical factors and a novel flexibility scoring concept, this paper studies the role of flexibility sources in the European electricity market. Additionally, with the help of the long-term and large-scale electricity market model HECTOR, the study assesses the interplay between the learning rate of a new technology (i.e. carbon capture and storage with flexible sequestration) and the system's flexibility that will be enhanced by the diffusion of the new flexible technology. Furthermore, the impact of the renewable energy mix on the electricity market's flexibility is studied by considering the dominance of a specific renewable energy technology (offshore and onshore wind) in the electricity market. The simulation results show that the system's flexibility can reach higher levels by 2050 if socio-technical parameters are included in HECTOR. A comparison of offshore and onshore wind-oriented scenarios highlights that in the offshore wind-oriented scenario, 3.43 TWh less renewable electricity is generated than in the onshore wind-oriented scenario, and that 16.2 Gigatons more of CO 2 are emitted than in the onshore wind-oriented scenario. Overall, it can be concluded that, in the long term, offshore wind provides 9 % higher flexibility to the system than onshore wind does.